How shocks affect stock market participation - Lorenz Meister; Karla Schulze (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
While there is a broad consensus in the literature that stock ownership is associated with individual characteristics, such as wealth, income, risk preferences, and financial literacy, less is known about the dynamics of stock market participation (SMP). Major fluctuations in SMP are oftentimes related to political events, economic shocks, and technological disruptions. We discuss the literature that investigates some of these shocks, as well as personal life circumstances that determine SMP across various demographic groups. Consolidating the literature allows us to identify systematic drivers into and out of stock ownership, along with its distributional consequences. Major forces behind SMP fluctuations are changes in participation costs and benefits, risk exposure, economic policy uncertainty, income uncertainty, peer effects, and windfall gains.
Keywords: 330; Kapitalanlage; Aktienmarkt; Anlageverhalten; Schock; Wirtschaftskrise; Marktlagengewinn; Altersgrenze; Arbeitslosigkeit; Deutschland